Diagnosis and treatment of Ludwig’s Angina: a case report - Farfán Gutiérrez, Christian (2018)
Ludwig’s angina is a life-threatening, rapidly progressive cellulitis that involves the floor of the mouth and the cervico-facial region. With induration and involvement of bilateral submandibular space, sublingual bilateral and submental. It presents with systemic and metabolic alterations. In general, no abscess or lymphadenopathy is seen in the classic descriptionHowever, progression to abscess formation within the space involved and contiguous spaces is common. The etiology in most cases is odontogenic. Treatment should prioritize the management of the airway, surgical drainage, elimination of the cause of infection, aggressive rapid antibiotic therapy and metabolic control with electrolytic water support. A female patient with a history of anemia presented odontalgia of the lower jaw teeth. She came the emergency room with an increase in volume of the lower third of the face. Predominantly on submandibular bilateral, submental and sublingual regions, as well as scanted general condition, fever, tachycardia, dysphagia, odynophagia and leukocytosis. The diagnosis of Ludwig’s angina was reached. Management of the airway, intraoral drainage, extraoral drainage, exodontia, immediate antibiotic therapy and electrolytic water support; were performed. She evolved favorably and was later discharged without complications.